PERANCANGAN KURIKULUM SEKOLAH MENENGAH KEJURUAN SEBAGAI PRANATA BUDAYA KERJA - Sutjipto (Jurnal Pendidikan dan Kebudayaan, 2019)
This study is to describe comprehensively the design of vocational high school curriculum as a work culture institution. The results of the study five things. First, the important content of work culture values for vocational school students. Second, curriculum developers are encouraged to modify the work culture, which leads to the values of hard work, work ethic, discipline, responsibility, creativity, cooperation, morality, to ethical and aesthetic standards. Third, curriculum developers are encouraged to redefine the essence of industrial work practices carried out by students. Fourth, the growth of work culture in schools is designed with shared commitment through systems, structures, regulations, and daily practices. Fifth, strengthening the work culture can be implemented in two ways, namely internalizing the values of work culture and creating a friendly school environment with a work culture. Study it conclude that the design of the vocational high school curriculum must generate students with capability in transforming moral and performance-based work culture institutions.